Design of Sundanese Script Through Android Based Interactive Game Applications - A T Cahyadi; I Kurniawan; R Widyanda (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this research is to utilize the latest android-based technology to introduce the Sundanese script to the public. so, this design can be used especially in the preservation of Sundanese culture which is judged by the development of the current era which has begun to be abandoned. Sundanese script with the concept of this android-based game to introduce the basics of Sundanese script as learning that can be used every day. Therefore, people can master the standard Sundanese script by using different methods and experiences for those who wish or find it difficult to absorb material using conventional methods. The research method used is descriptive qualitative with a project design process approach, data collection, and analysis to design. The results of this design through the method used starting from data collection to design, in the form of an android-based application prototype design that can be used directly. So that in this study it can be seen the use of technology is used as a learning media solution which is considered easy to use and can be useful for the community.